Lymphocytic hypophysitis masking a suprasellar germinoma in a 12-year-old Girl: a case report - Fehn, Marita; Bettendorf, Markus; Lüdecke, Dieter K.; Sommer, Clemens; Saeger, Wolfgang (Pituitary, 1999)
Case history, light and electron microscopic findings of a case of a lymphocytic hypophysitis in coincidence with a suprasellar germinoma in a 12-year-old girl are reported. The girl presented with a long time case history of diabetes insipidus and subsequent panhypopituitarism. Two years after the diagnosis of diabetes insipidus magnetic resonance imaging (MRI) showed a tumorous enlargement of the sellar content and pituitary stalk. A transnasal exploration was initially performed and revealed a lymphocytic hypophysitis. Light microscopy showed a dense infiltration of mature lymphocytes and plasma cells in the interstitium of the anterior pituitary gland. The stalk area could not be exposed to exclude a germinoma. One year later the lesion relapsed despite dexamethason therapy and a second operation by another neurosurgeon had to be performed. Light microscopy showed lymphocytic infiltrates, fibrosis and necrosis. The diagnosis was a lymphocytic hypophysitis again. Though transcranially exposed only pituitary tissue was removed. No infundibular mass became visible at surgery as shown by MRI. The girl developed five months later multiple cerebral lesions, which revealed to be a germinoma. Lymphocytic hypophysitis in children is very rare and a coincedence with a germinoma has not been described from histopathological aspect until now. The origin of the pituitary infiltration is discussed.